KH Maimun Zubair Gagasan dan Kiprahnya dalam Politik Islam di Indonesia - Nawal Nur Arafah (Journal on Education, 2022)
Kiyai has a significant influence among the people despite aligning a dual role as a caretaker of boarding schools as well as a politician. This article examines K.H. Maimun Zubair, the caretaker of the Al Anwar Sarang islamic boarding school and also the Chairman of the Sharia Assembly of the United Development Party (PPP). Holds the highest authority and full authority in determining the direction of party policy as a moral guardian and able to minimize the dynamics of PPP conflicts. Mbah Moen's presence in the PPP still exerts influence in political contestation in 2019. This is evidenced by the PPP's ability to pass political turbulence and be able to pass the 2019 elections by passing the parliamentary threshold. With charisma that is still maintained and the firmness of kiyai in holding the teachings of Al-ghazali, namely religious and state affairs, they must be placed in their respective positions, with good and balanced cooperation, so as to minimize conflicts in political parties. With charisma still maintained and the firmness of kiyai in religious and state affairs must be placed in its position and with good and balanced cooperation, so as to minimize conflicts in political parties.